Contexto literário, metaficção historiográfica e simulacro no Memorial de Saramago - Domingues, Kleber Henrique Alves (2018)
This work aims to present a study on the romance Baltasar and Blimunda by José Saramago (1982). At first, it will demonstrate how the romance is introduced in its literaty context, which will be defined according to Lukács‟ view about the history of romance art. According to Lukács, modern romance consolidates itself as expression of a counter-Ancien Regime emerging bourgeoisie, while Baltasar and Blimunda problematizes this condition presenting what would be considered an anti-bourgeois epopeia. After it, the analysis will focus a more recent literary context, presenting how Baltasar and Blimunda can be associated to theoric-critical inclinations which would be considered as “post-modern”; this way the principal focus will be metafiction historiographic concept, demonstrating how the opus referred produces an interesting re-reading of moments of the nation historiography. After it, this work will present some concepts of the philosopher Gilles Deleuze, especially simulacrum one, which might auxiliate on going along with some Saramago‟s aesthetic strategies. The subsistence and emergence of the simulacrum, and how it might reach reader‟s sensibility, will be demonstrated in the narration strategies, in the writing and irony styles of Saramago on referred romance. After all, this worf will presents a special passage of simulacrum emergence on the clímax of the romance, where figures marginalized by historical past emerge in a special way.